Redox Cycling on Recessed Ring-Disk Nanoelectrode Arrays in the Absence of Supporting Electrolyte. - Chaoxiong Ma; Contento, Nicholas M.; Bohn, Paul W. (Journal of the American Chemical Society, 2014)
In canonical electrochemical experiments, a high-concentration background electrolyte is used, carrying the vast majority of current between macroscopic electrodes, thus minimizing the contribution of electromigration transport of the redox-active species being studied. In contrast, here large current enhancements are achieved in the absence of supporting electrolyte during cyclic voltammetry at a recessed ring-disk nanoelectrode array (RRDE) by taking advantage of the redox cycling effect in combination with ion enrichment and an unshielded ion migration contribution to mass transport. Three distinct transport regimes are observed for the limiting current as a function of the concentration of redox species, Ru(NH), revealed through the strong dependence of ion transport on ionic strength. Behavior at low analyte concentrations is especially interesting. In the absence of supporting electrolyte, ions accumulate in the nanopores, resulting in significantly increased current amplification compared to redox cycling in the presence of supporting electrolyte. Current enhancements as large as 100-fold arising from ion enrichment and ion migration effects add to the 20-fold enhancement due to redox cycling, producing a total current amplification as large as 2000-fold compared to a single microelectrode of the same total area, making these RRDE arrays interesting for electrochemical processing and analysis.